Exploring the role of cell cycle regulation in human mature adipocyte dedifferentiation - Ostinelli, Giada; Gauthier, Marie-Frédérique; Vernoux, Nathalie; Bernier, Emilie; Dubé, Tristan; Marceau, Simon; Lebel, Stéfane; Tremblay, Marie-Ève; Tchernof, André (Frontiers in Cell and Developmental Biology, 2025)
BackgroundDedifferentiated fat (DFAT) cells have been used in regenerative medicine due to their multipotent potential. According to the literature, the process of adipocyte dedifferentiation is characterized by liposecretion which results in a fibroblastlike, proliferating cell population, with increased expression of genes related to cell cycle. A number of pathways have been implicated in the process, but the role of the cell cycle in adipocyte dedifferentiation has yet to be investigated. Here we characterize the process of liposecretion, the cellular features of DFAT cells and the role of the cell cycle.MethodsPrimary adipocytes and adipocyte-derived pluripotent cells (APC) were isolated from human adipose tissue and mature adipocytes were dedifferentiated in ceiling culture. The intracellular organization of DFAT and APC were compared using transmission electron microscopy (TEM), and the changes of intracellular lipid content over time were tracked with Oil Red O. Finally, we tested whether liposecretion is a cell cycle-dependent phenomenon by cultivating mature adipocytes in ceiling culture with or without four different inhibitors of the cell cycle (AraC, Irinotecan, Vincristine and RO-3306).ResultsDFAT cells were enriched in intracellular lipids, which are stored in small lipid droplets. In addition, liposecretion, which characterizes mature adipocyte dedifferentiation, is characterized by the rapid secretion of a large lipid droplet that is coated by a membrane. This phenomenon seems to be hindered by the presence of cyclin dependent kinase 1 (CDK1) inhibitor RO-3306.ConclusionBoth human adipose tissue depots undergo dedifferentiation in vitro, but visceral adipose tissue DFAT cells retain more lipids than subcutaneous-derived DFAT cells. Liposecretion is characterized by the rapid ejection of a membrane-wrapped lipid droplet. This phenomenon is dependent on CDK1 and likely relies on the presence of integrin-mediated cellular adherence.